Affection and its dimensions: Models contrasted through confirmatory factor analysis of PANAS Schedule - Flores Kanter, Pablo Ezequiel (2016)
Within self-report measures, one of the most mentioned scales in the scientific literature on emotions is the Positive and Negative Affect Schedule (PANAS). Taking into account previous research, the present work has a main objective, to replicate in a sample of Argentine university students the previous findings found in other countries about the factorial dimension of PANAS. For this, it was used the Confirmatory Factor Analysis. Although in general the results showed that the hierarchical, discriminant and convergent affection properties proposed by Watson (2000) cannot be fully corroborated. Thus, it is evident that the observable variables Alert and Excited have a cross weighting, affecting the overall adjustment of the models. Finally, the trifactorial model of the Affect is the one that presents better indices of adjustments, both for the oblique and orthogonal cases.